2002
DOI: 10.1038/ni815
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide exchange in domain 2 of CD4 is required for entry of HIV-1

Abstract: CD4, a member of the immunoglobulin superfamily of receptors that mediates cell-cell interactions in the immune system, is the primary receptor for HIV-1. The extracellular portion of CD4 is a concatenation of four immunoglobulin-like domains, D1 to D4. The D1, D2 and D4 domains each contain a disulfide bond. We show here that the D2 disulfide bond is redox-active. The redox state of the thiols (disulfide versus dithiol) appeared to be regulated by thioredoxin, which is secreted by CD4(+) T cells. Locking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
207
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(211 citation statements)
references
References 47 publications
4
207
0
Order By: Relevance
“…Indeed, if the surface-associated form of PDI can act as a redox-driven chaperone to unfold proteins after disulfide bond reduction, as has been shown for its endoplasmic reticulum counterpart (38), it may directly catalyze the conformational changes occurring within Env required to ultimately unmask the gp41 fusion peptide. Recently, the reduction of the second domain of CD4 was reported to be an obligatory step in CD4-dependent fusion (39). Our results raise the possibility that redox changes observed within CD4 may be the consequence of thiol/disulfide interchanges occurring within the CD4⅐CXCR4⅐Env complex after Env reduction by PDI.…”
Section: Fig 3 Thiol Content and Cxcr4 Binding Propertiesmentioning
confidence: 52%
“…Indeed, if the surface-associated form of PDI can act as a redox-driven chaperone to unfold proteins after disulfide bond reduction, as has been shown for its endoplasmic reticulum counterpart (38), it may directly catalyze the conformational changes occurring within Env required to ultimately unmask the gp41 fusion peptide. Recently, the reduction of the second domain of CD4 was reported to be an obligatory step in CD4-dependent fusion (39). Our results raise the possibility that redox changes observed within CD4 may be the consequence of thiol/disulfide interchanges occurring within the CD4⅐CXCR4⅐Env complex after Env reduction by PDI.…”
Section: Fig 3 Thiol Content and Cxcr4 Binding Propertiesmentioning
confidence: 52%
“…It has been shown that thiol͞disulfide exchange in integrin ␣ IIb ␤ III (11) as well as disulfide reduction in von Willebrand factor multimers (37) is necessary for hemostasis and regulating clot formation under high shear forces generated by blood flow. Even the mechanical process of HIV virus fusion and entry into helper T cells has been shown to require disulfide bond reduction in both gp120 of HIV (38) and the CD4 cell surface receptor (39).…”
Section: Resultsmentioning
confidence: 99%
“…One of several proteins that are susceptible for redox regulation is CD4 itself (11). It might be possible that the CD4-MHC class II interaction is altered upon redox changes in CD4 (28), resulting in different signal transductions into the cell and different outcomes of thymic selection or antigen presentation.…”
Section: Discussionmentioning
confidence: 99%